Anti-Hyperlipidemic Action of Zingiber officinale (Ginger) Juice in Alloxan Induced Diabetic Rats - Sultana, Selima; Akter, Shakil; Khan, Md Ismail (Ibrahim Medical College Journal, 2013)
Hyperlipidemia is an important modifiable risk factor contributing to atterosclerosis in diabetes mellitus. Zingiber officinale (ginger) widely consumed as spice is known for its hypoglycemic and hypochlosteremic actions. The present study was undertaken to investigate anti-hyperlipidemic action of ginger juice in alloxan-induced diabetic rats. Male Wister rats, 130-150 g wt, fed on standard diet and water ad libitum were divided into 4 groups (n=6 in each group): group I nondiabetic control, group II non-diabetic treated; group III diabetic control and group IV diabetic treated. Diabetes was induced by Inj. alloxan 150 mg Kg1 b.w., i.p. (group III & IV) on Day 2. Rats having blood glucose level of >7 mmol/l on day 5 (72 hrs after alloxan Inj.) were considered diabetic and selected for experimentation. Both non-diabetic and diabetic treated groups (Gr II & IV) received Zingiber officinale (ginger) juice (4 ml Kg1 b.w., p.o.) for 10 days (day 2-day 11) through Ryles tube. On Day 12, animals were sacrificed under light ether anaesthesia, blood was collected by cardiac puncture and serum separated for estimation of lipids. Zingiber officinale (ginger) juice significantly (p<0.01) decreased alloxan induced hyperglycemia (group IV), but had no effect on blood glucose level in normal rats (group II); significantly (p<0.001) reduced alloxan induced hyperlipidemia, but produced no significant lipid lowering effects in normal rats (group II). The results suggest a significant anti-hyperlipidemic action of Zingiber officinale (ginger) juice in alloxan induced diabetic rats. The findings may be clinically significant and exploited. DOI: http://dx.doi.org/10.3329/imcj.v6i2.14730 Ibrahim Med. Coll. J. 2012; 6(2): 55-58